PELATIHAN PENGGUNAAN APLIKASI QUIZIZZ PADA GURU-GURU SMP SWASTA ISLAM MUTHMAINNAH SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU - Jariyah, Ainun; Wao, Yosephina Payu; Lidi, Maria Waldetrudis; Daud, Maimunah H.; Mete, Yuliana Yenita; Priska , Melania; Gago, Jumilah; Wae, Veronika P. S. M.; Mei, Maria Fatima; Sani, Stefan Anselmus Lamen (LPPM Universitas Flores, 2024)
The objectives of this service include providing insight into the importance of online evaluation and improving teacher skills as service partners in creating and using the Quizizz application. The Quizizz benefit workshop for Muthmainnah Islamic Private Middle School teachers occurred on May 19 2024 at Muthmainnah Islamic Private School, Ende Regency, NTT. The workshop participants consisted of 15 Muthmainnah Islamic Private Middle School teachers. This training was provided by 8 lecturers from the Biology Education Study Program. The training methods the presenters use include direction, discussion and questions and answers, direct practice in the field and mentoring. Based on the results obtained from this activity, the training participants from Mutmainah Islamic Private Middle School responded positively. This can be seen when following the training, participants become enthusiastic and have increased creativity in making learning evaluations using Quizizz.